2018
DOI: 10.1016/j.eats.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Modified Latarjet Procedure Without Capsulolabral Repair for Failed Previous Operative Stabilizations

Abstract: The optimal management of recurrent anterior shoulder instability with significant glenoid bone loss continues to be a challenge. The high recurrence rates seen in arthroscopic Bankart repair in the presence of significant glenoid bone loss have led many surgeons to choose bony reconstructions to manage these injuries. The Latarjet procedure acts through the combination of 3 different mechanisms: the coracoid bone graft restores and extends the glenoid articular arc, the conjoint tendon acts as a dynamic sling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…The 14 studies analyzed in the systematic review included 883 patients. 2-8,10,11,14,16-18,21 The studies were primarily level 3 (n = 4) or level 4 (n = 10) evidence; of the 14 studies, 13 had a MINORS score greater than 80%. Of the studies that reported the participants’ sex, the majority were male (88%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 14 studies analyzed in the systematic review included 883 patients. 2-8,10,11,14,16-18,21 The studies were primarily level 3 (n = 4) or level 4 (n = 10) evidence; of the 14 studies, 13 had a MINORS score greater than 80%. Of the studies that reported the participants’ sex, the majority were male (88%).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies 2-5,8,11,14,17,18,21 reported return to sport at any level (Table 2 and Appendix Figure A1, available online), which ranged from 80% to 100% with the exception of 1 study (38%). 8 Eleven studies 2,3,6,7,10,11,14,16-18,21 reported return to sport at the previous level of play (Table 2 and Appendix Figure A2, available online), which ranged from 56% to 95% with the exception of 1 study (16%). The average time for return to sport ranged from 3.2 to 8.1 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The Latarjet procedure has been proven reliable to manage recurrent anterior shoulder instability with these bone defects. 1,8 Despite this, there was concern because of the high incidence of surgical complications associated with this procedure. Carbone et al 2 reported that scapular dyskinesis was found in 25% of patients who underwent a Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, common complications include coracoid graft nonunion. 8 Thus some arthroscopic techniques using iliac crest bone grafts have been described that challenge these complications and produce good clinical outcomes. 5,[9][10][11] All-arthroscopic iliac crest graft augmentation techniques have been reported, including those of Scheibel et al 10 using bio-compression screws, Taverna et al 11 using EndoButton devices, and Kalogrianitis et al 5 using tightrope devices.…”
Section: Discussionmentioning
confidence: 99%